PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI 2 DIMENSI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V SDN LAMBANG JAYA 01 - Uman, Usman; Ira Restu Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study developed a 2D animation learning media to enhance the learning motivation of fifth-grade students in the IPAS subject at SDN Lambang Jaya 01. The research was motivated by the low learning motivation caused by the lack of engaging and interactive learning media. The method used was Research and Development (R&D) with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects were fifth-grade students, with instruments including expert validation questionnaires, teacher and student response questionnaires, and student motivation questionnaires. The results of media, material, and language expert validations indicated a “highly feasible” category. Small group and field trials showed a significant improvement in students’ learning motivation. Therefore, this 2D animation media is considered feasible and effective for use in IPAS learning at the elementary school level.